Evaluating the effectiveness of adaptive antenna array in weight coefficients discretization - Moskalets, Mykola (Technology audit and production reserves, 2017)
Currently, there is a shortage of using radio resources in the world and there is an acute need for using additional physical resources that increase the bandwidth of communication channels and increase the productivity of mobile communication systems in general. The use of space-time physical parameters in the organization of multiple access (STA) of subscribers is becoming relevant. The methods of subscriber stations (SSs) STA to the resources of the base station (BS) are based on the use of -element adaptive antenna arrays (AAA). The methods and algorithms of AAA synthesis are based on the evaluation of the complex vector of weight coefficients (VWC) included in the reception paths of each antenna element (AE) and controlled by various algorithms. Therefore, the object of research is the process of discretization of the weight coefficients in the adaptive antenna array. The main disadvantage identified during the audit in this study is the calculation of the computational complexity of the quantization algorithm for weight coefficients for different variations in the parameters of the signal-interference situation at the AAA input. Complex, systemic evaluation of the effectiveness of AAA functioning taking into account the chosen criterion of the effectiveness of the AAA operation, using the procedure for quantizing the weight coefficients, is possible with a broader and precise specification of the parameters of the operating signal-interference environment. This will allow to obtain reliable results. The required dimensionality of the adaptive array antenna weights is determined depending on the ratio of the total interference power to the internal noise power at the input of the bandpass filter, based on the allowable decrease in the average output signal-to-interference-plus-noise ratio. On the basis of the obtained analytical estimation of the loss rate, an expression for calculating the required quantizer capacity is proposed. It is possible to show that, regardless of the amount of allowable losses, the required quantizer capacity is increased by 1 bit with an increase in the input interference/noise ratio by 6 dB.